Camilo Henríquez: theater, republicanism and modernity (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
This article approaches the work of Friar Camilo Henríquez, specifically the play The Camila or the Patriot of South America, from the assumption that aesthetic principles are subordinate to the illustrated modern and republican ideas, who Fray Camilo devoted most of his life to defend and disseminate. From the analysis of La Camila, the article unveils the different textual marks through which the author disseminated republican ideas and established, in an assimilation fashion, a modern Indian subject. This happens in a reception context in which colonialism and modernity appear to be simultaneous, and therefore republican thought becomes utopian
Keywords: Modern subject; Republican thought; Modernity; Sociability; Asynchrony